2020
DOI: 10.1177/0092055x20954263
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Remote Learning Transition in Spring 2020: Class Structures, Student Perceptions, and Inequality in College Courses

Abstract: The COVID-19 pandemic forced all face-to-face college courses to transition to remote instruction. This article explores instructional techniques used in the transition, student perceptions of effectiveness/enjoyment/accessibility of those techniques, barriers that students faced due to the transition, and race/class/gender inequality in experiencing those barriers. We used surveys in introductory courses by two instructors (the authors) to compare students’ reactions to our transitions and the transitions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
255
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(274 citation statements)
references
References 21 publications
10
255
2
7
Order By: Relevance
“…More surprisingly, students taking nFTF subjects reported even higher overall satisfaction and willingness to recommend this subject to their friends than students taking FTF subject. In contrast with reports indicating university students’ worry, distress, and discontent with e-learning [ 56 , 57 ], this study showed high levels of satisfaction among students. This nFTF mode of service learning incorporated helpful practices that facilitated online learning, such as adjusting teaching content and activities for an effective delivery of teaching information, providing adequate support from teacher and teaching assistants to students, and preparing contingency plans to deal with unexpected incidents due to technical problems [ 58 ].…”
Section: Discussioncontrasting
confidence: 99%
“…More surprisingly, students taking nFTF subjects reported even higher overall satisfaction and willingness to recommend this subject to their friends than students taking FTF subject. In contrast with reports indicating university students’ worry, distress, and discontent with e-learning [ 56 , 57 ], this study showed high levels of satisfaction among students. This nFTF mode of service learning incorporated helpful practices that facilitated online learning, such as adjusting teaching content and activities for an effective delivery of teaching information, providing adequate support from teacher and teaching assistants to students, and preparing contingency plans to deal with unexpected incidents due to technical problems [ 58 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Mseleku (2020) found that the stress of ERT often resulted in depression, anxiety, and other mental-health related issues; and seriously impacted student learning and satisfaction. Other researchers support these findings ( Gillis & Krull, 2020 ; Aguilara, 2020 ; Bozkurt et al., 2020 ).…”
Section: Literature Reviewmentioning
confidence: 69%
“…Many studies address the issue of technology challenges, particularly in the context of students who do not have adequate access to the internet, computers/printers, or lack technological skill to negotiate the online environment (e.g., Aboagye et al., 2020 ; Shim & Song, 2020 ; Trust & Whalen, 2020 ; Wiltse et al., 2020 ; Mseleku, 2020) . Gillis and Krull (2020) discovered that internet and technology barriers were widespread. Students from rural areas and low-income families in particular had difficulty ( Mseleku, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As they note, the transition to remote online learning has prompted the need to enhance, expand, and create new theoretical approaches that bolster our ability to ensure student success amid any crisis. This line of inquiry will inform the ongoing debate regarding the value of different instructional modalities for online instruction (Gillis & Krull, 2020).…”
Section: The Messages In the Essaysmentioning
confidence: 95%